2020
DOI: 10.3389/fpsyt.2020.579538
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Plasma Metabolites and Psychometric Scores Among Children With Developmental Disabilities: Investigating Sex-Differences

Abstract: Background: Developmental disabilities are defined by delays in learning, language, and behavior, yet growing evidence has revealed disturbances in metabolic systems that may also be present. Little is known about whether these metabolic issues contribute to the symptoms or severity of these disabilities, or whether sex plays a role in these associations, given that boys are disproportionately affected by some developmental disabilities. Here we sought to investigate the correlation between psychometric scores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…Specifically, in those with DD, we found involvement of ATP and other energy metabolites. Previous studies show elevations in the TCA and energy pathway metabolites in both urine [ 21 ] and plasma [ 13 , 14 ]. Studies examining the characteristics of those with ASD and mitochondrial disorder demonstrate a high incidence of DD, particularly motor delay [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, in those with DD, we found involvement of ATP and other energy metabolites. Previous studies show elevations in the TCA and energy pathway metabolites in both urine [ 21 ] and plasma [ 13 , 14 ]. Studies examining the characteristics of those with ASD and mitochondrial disorder demonstrate a high incidence of DD, particularly motor delay [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Children with DD have been shown to have increased glycolic and 3-hydroxyisobutyric acid and decreased palmitic acid [ 21 ] in urine and elevated acetate, glutamate, lactate and tricarboxylic acid (TCA) cycle metabolites in plasma [ 13 ]. Interestingly, one study that included DD and ASD participants demonstrated that cognitive function, adaptive skills, and aberrant behavior were related to some of these same metabolites [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The repeated association of energy metabolism with many aspects of ASD is not surprising given the high rate of mitochondrial dysfunction associated with ASD [ 10 , 11 ]. Furthermore, the link to neurodevelopment and language is not surprising as previous studies have linked developmental delays to abnormal CAC and energy pathway biomarkers in urine [ 54 ], plasma [ 55 , 56 ], and CSF [ 34 ]. Children with ASD and mitochondrial disease appear to have two developmental profiles, those with developmental delays, including motor delay, and those that manifest NDR [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, one could imagine two metabolites that have the same concentrations in TD and ASD, but whose correlation changes with age or other conditions (e.g, diet; example [ 48 ]). Much of the literature on biomarkers of ASD and/or IDD has focused on the search for individual molecules, or statistical combinations of molecules, which are predictive of ASD-related morbidity or diagnosis [ 16 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ]. However, few metabolomic studies have moved beyond individual, isolated biomarkers, focusing instead on metabolic pathway analysis, in which whole metabolic pathways are analyzed for significant changes.…”
Section: Discussionmentioning
confidence: 99%